PROFESSOR T.I. PONIMANSKA’S METHODOLOGICAL HERITAGE IN THE DEVELOPMENT OF THE THEORY AND PRACTICE OF PRE-SCHOOL EDUCATION IN UKRAINE - Марчук, Галина (SWorldJournal, 2024)
The article analyses the pedagogical ideas of famous ukrainian educator and scholar Tamara Illivna Ponimanska; highlights her scholarly-pedagogical heritage into the development of the theory and practice of preschool education in Ukraine ; particularly,